Study of recycling awareness among public and private university students / Ayub Saidi - Saidi, Ayub (Faculty of Architecture, Planning and Surveying, 2013)
This study was undertaken in order to discover the tertiary student perception, which compared between public and private segment, towards recycling awareness. The focus of this study is to investigate the usage pattern of recycling bins and any other factors directly related to this matter, compare and analyze the effectiveness of recycling program with current situation and to give recommendation and suggestion on how to maximize and overcome the several issues regarding to recycling program in public and private university. The respondent involved were 400 students which came across from four (4) selected public and private universities. UiTM Shah Alam and University of Malaya represent public university while MSU and UNISEL represent private university. The method used was distribution of questionnaires which contained of demographic information about the respondent, their usage of recycling bins and recycling awareness. The result from this study are mixed, the standout result is most respondent still does not use the recycling facilities provided effectively. This shows that the respondents still do not willing enough to participate in recycling campaign, even at tertiary level. As a reaction to this, some suggestion were proposed by the researcher to university management for them to take further action.